2001
DOI: 10.2527/2001.7971742x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of milk yield and fertility traits in Holstein-Friesian cattle on large-scale Kenyan farms.

Abstract: Purebred Holstein-Friesian cows are the main exotic breed used for milk production on large, medium, and small farms in Kenya. A study was undertaken on seven large-scale farms to investigate the genetic trends for milk production and fertility traits between 1986 and 1997 and the genetic relationships between the traits. This involved 3,185 records from 1,614 cows, the daughters of 253 sires. There was a positive trend in breeding value for 305-d milk yield of 12.9 kg/ yr and a drop in calving interval of 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
71
16
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 26 publications
(34 reference statements)
35
71
16
1
Order By: Relevance
“…The phenotypic correlations between AFC and milk yield were very small and negative (−0.05). It is in accordance with other studies in which AFC and milk yield were estimated as small and negative (−0.20 to −0.09) (Ruiz-Sánchez et al, 2007;Ojango and Pollott, 2001;Nilforooshan and Edriss, 2004). However, Teke and Murat (2013) reported the moderate positive correlation between AFC and milk yield (r = 0.32; P<0.001).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The phenotypic correlations between AFC and milk yield were very small and negative (−0.05). It is in accordance with other studies in which AFC and milk yield were estimated as small and negative (−0.20 to −0.09) (Ruiz-Sánchez et al, 2007;Ojango and Pollott, 2001;Nilforooshan and Edriss, 2004). However, Teke and Murat (2013) reported the moderate positive correlation between AFC and milk yield (r = 0.32; P<0.001).…”
Section: Resultssupporting
confidence: 91%
“…The oldest primiparas were briefly used for milk production, which influenced their lifetime performance. Age at first calving determines the beginning of the cow's productive life and influences it's lifetime productivity (Ojango and Pollott, 2001). Ojango and Pollott (2001) and Ruiz-Sánchez et al (2007) indicated that earlymaturing heifers were better milk producers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values were higher than those reported by Ojango and Pollott (2001) and Kadarmideen et al (2000). Nevertheless, some authors (Estrada-León et al, 2008;M'hamdi et al, 2010;Ríos-Ultrera et al, 2010a) report higher repeatability values (0.120-0.180).…”
Section: Discussionmentioning
confidence: 66%
“…Smallholder systems of dairy production in Kenya have been extensively characterized under the Smallholder Dairy Development Programme (ILRI, 2004). Large-scale commercial farms operating in the country as either dairy or dual-purpose units have also been described (Kahi, 2000;Ojango and Pollott, 2001). These systems are highly mechanized, tend to raise pure-bred exotic (B. taurus) breeds, and produce large quantities of dairy products to which they add value.…”
Section: Systems Of Dairy Production and The Main Dairy Genotypesmentioning
confidence: 99%